2001
DOI: 10.1182/blood.v98.8.2498
|View full text |Cite
|
Sign up to set email alerts
|

Immunophenotypic analysis of hematogones (B-lymphocyte precursors) in 662 consecutive bone marrow specimens by 4-color flow cytometry

Abstract: Bone marrow hematogones (B-lymphocyte precursors) may cause problems in diagnosis because of their morphologic and immunophenotypic similarities to neoplastic lymphoblasts. The purposes of this prospective, multiparametric flow cytometry study were to quantify hematogones across age groups and a spectrum of clinical conditions, to identify factors that affect the relative quantity of hematogones, and to compare their immunophenotype with that of neoplastic lymphoblasts. A total of 662 consecutive marrow specim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

20
292
3
18

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 338 publications
(333 citation statements)
references
References 40 publications
20
292
3
18
Order By: Relevance
“…3,5 Morphological evaluation of BM smears confirmed that at the level of 5% or more hematogones were conspicuous and likely to be confused with ALL relapse as reported previously. 3 However, their immunophenotypic features, reported in Table 2, were always consistent with typical B cell precursors. Taking into consideration immunophenotypic features, chimerism status, MRD results and X chromosome inactivation analysis, B cell precursor expansion appeared clearly as non-malignant state.…”
mentioning
confidence: 66%
See 2 more Smart Citations
“…3,5 Morphological evaluation of BM smears confirmed that at the level of 5% or more hematogones were conspicuous and likely to be confused with ALL relapse as reported previously. 3 However, their immunophenotypic features, reported in Table 2, were always consistent with typical B cell precursors. Taking into consideration immunophenotypic features, chimerism status, MRD results and X chromosome inactivation analysis, B cell precursor expansion appeared clearly as non-malignant state.…”
mentioning
confidence: 66%
“…2 Hematogones exhibit a typical complex spectrum of lymphoid antigen differentiation extending from early B cell precursors to mature surface immunoglobulin-bearing B cells, lack aberrant antigen expression and do not exhibit clonal immunoglobulin or TCR gene rearrangements. 2,3 Their increase has been observed in marrow regenerative states following chemotherapy or BM transplantation and may cause diagnostic confusion particularly after treatment for ALL because of hematogones' similarities to neoplastic lymphoblasts. 3 Expansion of hematogones may be persistent, for 2 years after completion of chemotherapy for ALL and for more than 1 year following BM transplantation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…distinguishing leukemia from hematogones [13]. In our case, the bone marrow was occupied by nearby 85% blasts, indicating a possible malignant state.…”
Section: The Percentage Of Leukemic Cells In Bone Marrow Cells Is An mentioning
confidence: 85%
“…Their presence has been noted in children with different hematological (red blood aplasia, SchwachmanDiamond syndrome, amegakaryocytic thrombocytopenia, hereditary spherocytosis) and nonhematological (retinoblastoma, viral infections, HIV, Gaucher disease, Ewing's sarcoma) disorders [1,2]. Their morphology and immunophenotype (CD19, CD10, CD34 surface antigen, and nuclear terminal deoxynucleotidyl transferase/TdT positive) is similar to that of B-precursor cells [3,4]. Occasionally, an hematogone increase may mimic acute lymphoblastic leukemia (ALL), raising diagnostic problems [5].…”
Section: Introductionmentioning
confidence: 99%